1995
DOI: 10.1111/j.1432-1033.1995.0741h.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning and Tissue‐specific Regulation of Expression of Rat Calcium‐binding Protein 65/67

Abstract: We isolated a cDNA encoding the rat membrane-associated 65167-kDa calcium-binding protein, CBP 65/67, from a A ZAP I1 cDNA-expression library of rat liver by immunoscreening using monospecific polyclonal anti-(CBP 65/67) antibodies and monoclonal anti-(CBP 65/67) IgG. The product of this cDNA expressed in Escherichia coli was confirmed as CBP 65167 both by immunostaining and by comparison of the molecular mass with the CBP 65/67 isolated from rat liver by SDSPAGE. The cDNA sequence and the deduced amino acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…To validate the experiment, vesicles bound on magnetic beads with [21,40]. In rat liver, annexin A6 is a membrane-associated protein [12,41]. Some annexins can interact with integral membrane proteins, and they also seem to be part of signaling pathways in the cell [42].…”
Section: Discussionmentioning
confidence: 99%
“…To validate the experiment, vesicles bound on magnetic beads with [21,40]. In rat liver, annexin A6 is a membrane-associated protein [12,41]. Some annexins can interact with integral membrane proteins, and they also seem to be part of signaling pathways in the cell [42].…”
Section: Discussionmentioning
confidence: 99%
“…The coding region was polymerase chain reaction-amplified and generated a 2.0-kilobase pair annexin VI cDNA fragment (26) that was cloned into a mammalian expression vector (pcDNA3.1ϩ; Invitrogen) to generate pcDNAanx6. DNA sequence analysis using a Dye Terminator Cycle Sequencing reaction kit (PerkinElmer Life Sciences) together with T7, SP6 (Promega), and internal annexin VI primers confirmed the full-length and wild type rat annexin VI cDNA sequence in pcDNAanx6.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, one of these proteins was identified as annexin A6 [45]. Identification of other proteins from this fraction is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 also shows a comparison between the crude membrane fraction and highly purified liver plasma membranes with regard to the content of CEACAM 1. If the Triton X-100 insoluble pellet is further treated with suitable reagents such as EGTA, urea/4% CHAPS mixture, or SDS, socalled detergent-insoluble proteins can be extracted [44,45]. In previous experiments, we showed that membraneassociated annexin A6 can be solubilized by simple calcium-complexing with EDTA or EGTA (not shown here, cf.…”
Section: Fractionation Of Purified Liver Plasma Membranesmentioning
confidence: 99%
See 1 more Smart Citation